Effectiveness of Heat Detection Patches for Determining Cyclicity Status in Peripubertal Heifers - S. K. Johnson; J. R. Jaeger (Kansas Agricultural Experiment Station Research Reports, 2016)
Response to most estrous synchronization programs is improved in cycling females, compared to pre-pubertal heifers or anestrus cows. Cycling status is often monitored for research purposes by measuring progesterone concentrations in serum. Producers may want to use information on cyclicity status when determining which estrous synchronization program to use or as a component of their heifer selection. Heat detection patches are routinely used to aid or reduce time needed for heat detection. The most data on their use is for a 3 to 5-day period after estrous synchronization. Little information is available on retention of patches for longer time periods or how they may compare with serum progesterone for determining cyclicity status. Therefore, the objective of the current study was to compare Standing Heat and Estrotect heat detection patches with serum concentrations of progesterone for identifying cycling (pubertal) heifers before the start of the breeding season.
Keywords: Beef Cattle Research